Design and Implementation of an Arduino-Based PIR Sensor System for Automated Bird Pest Control in Agricultural Areas - Ade Sumaedi; Angelina Hadriani; Agus Suhendi (Al'Adzkiya, 2026)
Indonesia relies heavily on agriculture as a fundamental pillar of its economy, with a large proportion of the population depending on crop cultivation, particularly rice farming. However, farmers frequently encounter recurring challenges each planting season, including attacks from various pests such as sparrows that feed on ripening rice grains. Traditionally, farmers use simple manual deterrent tools made from recycled cans hung around the rice field and connected with ropes that must be pulled to create noise. This conventional approach requires continuous human effort and is often ineffective, allowing birds to consume significant portions of the crop before harvest. As a result, farmers may experience losses reaching approximately 642 kilograms within a seven-month cultivation period. In response to this problem, this study proposes the development of an automated bird repellent system based on an Arduino microcontroller integrated with a Passive Infrared (PIR) sensor to detect bird movement through infrared radiation. When motion is detected, a buzzer is activated to generate sound that scares birds away from the field. The implementation of this automated system helps prevent birds from approaching the rice plants before harvest, thereby significantly reducing crop damage and eliminating farmer lossesKeyword : Hama Burung, Mikrokontroler Arduino, Sensor PIR, Buzzer, LCD I2C